2020
DOI: 10.2196/20847
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Patient Engagement and Depressive Symptoms Among People Living With HIV in a Mobile Health Intervention: Secondary Analysis of a Randomized Controlled Trial

Abstract: Background Associations between higher levels of patient engagement and better health outcomes have been found in face-to-face interventions; studies on such associations with mobile health (mHealth) interventions have been limited and the results are inconclusive. Objective The objective of this study is to investigate the relationship between patient engagement in an mHealth intervention and depressive symptoms using repeated measures of both patient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…The participants in the intervention groups had a moderate level of patient engagement. The cumulative completion rates were 50.6%, 51.5%, and 50.8% at 1, 2, and 3 months, respectively, in the intervention group, which were comparable to other mHealth interventions [59]. The positive relationship between patient engagement and health outcomes has been confirmed in our previous study [59].…”
Section: Practical Implicationssupporting
confidence: 82%
“…The participants in the intervention groups had a moderate level of patient engagement. The cumulative completion rates were 50.6%, 51.5%, and 50.8% at 1, 2, and 3 months, respectively, in the intervention group, which were comparable to other mHealth interventions [59]. The positive relationship between patient engagement and health outcomes has been confirmed in our previous study [59].…”
Section: Practical Implicationssupporting
confidence: 82%
“…Seventeen studies evaluated digital interventions that were unguided (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). Of these, nine reported a positive association between engagement and mental health outcomes (33, 34, 36, 39-41, 43, 47, 49) while eight did not find a significant association (35,37,38,42,(44)(45)(46)48).…”
Section: Unguided Vs Guided Interventionsmentioning
confidence: 99%
“…Of the 35 studies, 14 (40%) reported evidence that greater engagement with DMHIs was associated with statistically significant improvements in mental health symptoms at postintervention, and this was consistent across all engagement measures used if multiple measures were used in a single study (33, 34, 36, 39, 40, 50-52, 54, 55, 61, 63, 65, 66). Five studies (17.1%) reported mixed findings, where improvements in the primary mental health outcome were associated with some, but not all, measures of engagement (37,43,47,49,57). Sixteen studies (45.7%) did not find any significant association between engagement and post-intervention mental health outcomes (20, 35, 38, 41, 42, 44-46, 48, 53, 56, 58-60, 62, 64).…”
Section: Narrative Synthesis Of the Effect Of Engagement On Mental Health Outcomesmentioning
confidence: 98%
“…In the remaining 23 studies, participants were not formally diagnosed with a mental health condition but were screened for symptoms indicative of mental disorders. Of these studies, 12 reported a positive association between engagement and the primary mental health outcome (33,36,40,41,43,47,49,50,52,57,63,65) while the other 11 did not find a significant association (37, 38, 42, 44-46, 48, 58, 59, 62, 64).…”
Section: Mental Health Diagnostic Statusmentioning
confidence: 99%
See 1 more Smart Citation